Scaled-up continuous up-flow microbial fuel cell based on novel embedded ionic liquid-type membrane-cathode assembly. (15th April 2016) - Salar-García, M.J.; Ortiz-Martínez, V.M.; Baicha, Z.; de los Ríos, A.P.; Hernández-Fernández, F.J.
Abstract: The capacity of MFCs (microbial fuel cells) to produce electricity from various substrates and wastes has drawn the attention of the scientific community in the last decades. Thus, this technology has become the focus of many research studies trying to improve its performance by investigating alternative materials and determining optimal operating conditions. In this work, a new single-chamber air-cathode microbial fuel cell configuration has been developed to operate in continuous mode with vertical up-flow. This design incorporates a novel embedded ionic liquid-based membrane-cathode assembly working as separator. The ionic liquids selected for the present work are triisobutyl(methyl)phosphoniumtosylate, [PI4, I4, I4, 1 + ][TOS − ], and methyltrioctylammonium chloride, [MTOA + ][Cl − ]. MFC performance is investigated in terms of electricity production and wastewater treatment for various feed flow rates. The results show that [PI4, I4, I4, 1 + ][TOS − ] outperforms [MTOA + ][Cl − ] when used as part of the separator due the conductivity of its anion and cation. For a feed flow rate of 0.25 mL min −1, [PI4, I4, I4, 1 + ][TOS − ] offers a maximum power density of 12.3 W m −3 anode versus 6.8 W m −3 anode achieved by the [MTOA + ][Cl − ]-based MFC, and also provided the highest percentage of chemical oxygen demand removal (60%). For the same ionic liquid, MFC power output increases as feed flow decreases. Highlights: New up-flow single-chamber MFC design in continuous mode. Application of novel embedded IL-based membrane-cathode assembly in scaled-up MFCs. Embedded [PI4, I4, I4, 1 + ][TOS − ]-based PIM achieves a power output of 12.3 W m −3 anode . 60% of COD removal is obtained using embedded [PI4, I4, I4, 1 + ][TOS − ]-based assembly. Low feed flow rates improve MFC performance in up-flow continuous mode.